Molecular, Biological and Structural Features of VL CDR-1 Rb44 Peptide, Which Targets the Microtubule Network in Melanoma Cells - Girola, Natalia; Resende-Lara, Pedro T.; Figueiredo, Carlos R.; Massaoka, Mariana H.; Azevedo, Ricardo A.; Cunha, Rodrigo L. O. R.; Polonelli, Luciano; Travassos, Luiz R. (Frontiers in Oncology, 2019)
Microtubules are important drug targets in tumor cells, owing to their role in supporting and determining the cell shape, organelle movement and cell division. The complementarity-determining regions (CDRs) of immunoglobulins have been reported to be a source of anti-tumor peptide sequences, independently of the original antibody specificity for a given antigen. We found that, the anti-Lewis B mAb light-chain CDR1 synthetic peptide Rb44, interacted with microtubules and induced depolymerization, with subsequent degradation of actin filaments, leading to depolarization of mitochondrial membrane-potential, increase of ROS, cell cycle arrest at G2/M, cleavage of caspase-9, caspase-3 and PARP, upregulation of Bax and downregulation of Bcl-2, altogether resulting in intrinsic apoptosis of melanoma cells. The in vitro inhibition of angiogenesis was also an Rb44 effect. Peritumoral injection of Rb44L1 delayed growth of subcutaneously grafted melanoma cells in a syngeneic mouse model. L1-CDRs from immunoglobulins and their interactions with tubulin-dimers were explored to interpret effects on microtubule stability. The opening motion of tubulin monomers allowed for efficient L1-CDR docking, impairment of dimer formation and microtubule dissociation. We conclude that Rb44 VL-CDR1 is a novel peptide that acts on melanoma microtubule network causing cell apoptosis in vitro and melanoma growth inhibition in vivo.